Development of portable temperature detector using Arduino: article / Muhammad Amirul Hafiz Jaaffar - Jaaffar, Muhammad Amirul Hafiz
This paper is about a portable device for temperature detecting based on Arduino UNO board and LM35 temperature sensor. This device allows users to read the real-time temperature value from the sensor; to display the temperature reading at the LCD display panel; the user can set the require temperature to trigger an LED light; Some experimental results are carried out to determine the accuracy and persistency of the device performance.